Battery Health Monitoring System Lithium-Ion Based on Fuzzy Logic - Yogo Bekti Firmanto; Ahmadi Ahmadi; Rangsang Purnama; Wiwiet Herulambang (JEECS (Journal of Electrical Engineering and Computer Sciences), 2024)
Batteries that can store electrical energy and are easy to carry make them the most practical technology choice as an electricity source. Even so, lithium-ion batteries are not free from the risk of damage when used. Therefore, a Lithium-ion battery health monitoring system was created. This system uses the INA219 sensor as a current and voltage detector and the DS18B20 sensor as a temperature detector. Arduino as a data process. The test results show that all components function well. In battery capacity testing, the highest error was 1.8%. For the DS18B20 sensor as a temperature sensor, an error of 2.4% was obtained. Testing capacity against temperature on the battery when the temperature was 25 C, the current was 485mAh; when the temperature was 44.8 C, the current was 550mAh, there was a difference of 65mAh or 11%. This difference corresponds to the difference in battery capacity. Testing using the Fuzzy Logic method was carried out on 3 batteries with different capacities to obtain the State of Health (SOH) value for each battery. Testing is carried out in real-time, as well as Matlab simulation. In battery test 1, with a capacity of 2200mAh and the highest temperature of 32.1 oC, the device's State of Health (SoH) was 90%, and Fuzzy Matlab was 87.6%. Battery 2, 1500mAh capacity with the highest temperature of 33.4oC obtained State of Health (SOH) of 60%, Fuzzy Matlab 60%. Battery 3 Capacity 2200mAh, Highest temperature 32.2 oC, State of Health (SOH) of 90%, Fuzzy Matlab 87.6%. The test results show that the overall error is still below 5%. A properly functioning Internet of Things (IoT) system can display information on lithium-ion batteries' State of Health (SoH) on devices and smartphones.